2023
DOI: 10.3389/fendo.2023.1255656
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between triglyceride-glucose index and thyroid hormones on coronary artery disease risk in patient with euthyroid

Li Li,
Gaojun Cai,
Wei Lu
et al.

Abstract: BackgroundTriglyceride-glucose (TyG) index is an effective indicator in indentifying in pre-diabetes, diabetes, and coronary artery disease (CAD). However, the value of TyG index combined with thyroid hormones (THs) to affect CAD has not been fully evaluated. Here, we investigated the association between TyG index and THs and further studied the impacts of TyG index and THs on CAD in euthyroid.MethodsSubjects (1,297) with euthyroid who underwent selective coronary angiography (CAG) were enrolled in the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Previous studies have showed that FT3 is negatively correlated with coronary artery disease (40,41), and higher FT3 is crosssectionally associated with higher total HDL particle concentration and with lower HDL particle size in euthyroid individuals (42). Furthermore, T3 has been found to influence atherosclerosis through thyroid hormone receptors, which regulate the atherosclerotic process independently of the lipid profile (43).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have showed that FT3 is negatively correlated with coronary artery disease (40,41), and higher FT3 is crosssectionally associated with higher total HDL particle concentration and with lower HDL particle size in euthyroid individuals (42). Furthermore, T3 has been found to influence atherosclerosis through thyroid hormone receptors, which regulate the atherosclerotic process independently of the lipid profile (43).…”
Section: Discussionmentioning
confidence: 99%